Copper Isotope Ratio Measurements of Cu-Dominated Minerals Without Column Chromatography Using MC-ICP-MS - Zhang, Yan; Bao, Zhian; Lv, Nan; Chen, Kaiyun; Zong, Chunlei; Yuan, Honglin (Frontiers in Chemistry, 2020)
This study performed a series of comparable experiments (with or without column chromatography) to assess whether non-deviated Cu isotope ratios can be acquired directly by Nu Plasma II multi-collector inductively coupled plasma-mass spectrometry (MC-ICP-MS) using standard-sample bracketing with Ga as internal mass bias correction model (C-SSBIN) without column chromatography. Twelve Cu-dominated minerals (copper plate, native copper, chalcopyrite, bornite, chalcocite, digenite, covellite, tetrahedrite, azurite, malachite, atacamite, and cyanotrichite) displayed little drift in δ65Cu values compared with those of minerals with column chromatography, with Δδ65Cuwithout-with ranging from -0.04 ‰ to +0.02 ‰. This implies that Cu isotope ratios in Cu-dominated minerals can be achieved without column chromatography, due to the simple matrix and the stability of the machine by using C-SSBIN mode. The effect of acidity and concentration mismatch, as well as the matrix effect, were rigorously evaluated using the Nu Plasma II MC-ICP-MS with a wet-plasma mode in the State Key Laboratory of Continental Dynamics (SKLCD). Finally, a long-term reproducibility of better than ±0.03 ‰ (n = 38) was achieved by repeatedly measuring chalcopyrite without column chromatography over four months.